Levels of forage meal in integral meals for calves - Plaza, Joaqu?n; Ibalmea, Rolando; Mart?nez, Yordan (Cuban Journal of Agricultural Science, 2011)
Thirty-two Holstein calves, of 7 d of age and average liveweight of 35 kg, were used in a random block design with eight replicates. The calves were put in individual craddles up to 90 d of age and given integral rations, with different levels of meal of grass mixed with the concentrate in integral form in the following treatments: A) 10 %, B) 20 %, C) 30 %, and D) 40 %. All the calves were given three liters of fresh milk, on time a day from 7 to 49 d, and the integral rations were consumed ad libitum, to evaluate the level of fiber of the ration in the performance of the calves In. the periods from 7 to 49 d, and from the weaning up to 90 d of age, there were not differences between treatments in liveweight and daily weight gain. The rations had high level of protein and energy for this type of animals, which could have disguised the effect of the level of fiber. The intakes of DM, CP and ME per kg P 0.75 and the DM conversion did not differ between treatments, but the CF intakes were higher (P < 0.001), as the level of fiber was higher in the ration. It is concluded that the inclusion of 10 to 40 % of forage meal in the integral ration for calves permits to attain a good performance, with weight gains in the post-weaning stage of approximately 600 g/d and an acceptable ruminal development to have an early weaning at 49 d of age, when the rest of the nutrients from the ration are not a limitation. Key words: calves, forrage meal, integral rations.